Lessons from the Santa Monica Mountains: Continuing the cycle of conservation - Cooper, Daniel S.; Katz, Nurit D.; Demirci, Brianna; Osborn, Fiona M. (Frontiers in Sustainable Cities, 2022)
Spanning more than 73 km across two counties at the western border of the Los Angeles metropolitan area, the Santa Monica Mountains represent both a major landform as well as a unique urban-adjacent open space for millions of residents throughout southern California. Critically, they are essential for the maintenance of high levels of biodiversity within a global biodiversity hotspot that includes a major metropolis. The Los Angeles County portion of the Santa Monica Mountains (LASMM), spanning approximately 62 km from the Los Angeles River at the eastern edge of Griffith Park to the Los Angeles – Ventura County Line, contains substantial public open space, protected from encroaching development in the growing metropolis. In order to understand how these protected areas were established, we gathered information regarding over 3,000 parcels of public open space and their acquisition dates and owners, and examined the history of land conservation in the LASMM to determine the roles and relationships of key stakeholders. These stakeholders have included residents, activists, scientists, legislators, non-governmental organizations (NGOs), and land management agencies. We suggest that there is a virtuous cycle, or positive feedback loop over time, as open space protection is informed by, and influences, advocacy, land use policies, and habitat conservation. This interplay of stakeholders has been refined over several decades, and may offer lessons for other regions working to produce similar results in durable open space conservation.